Left Atrial Dilatation and Reduced Left Ventricular Ejection Fraction Are Associated With Cardioembolic Stroke - Hosseini Farahabadi, Maryam; Milani-Nejad, Shadi; Liu, Shimeng; Yu, Wengui; Shafie, Mohammad (Frontiers in Neurology, 2021)
Objective: Left atrial (LA) dilatation and heart failure are independent risk factors for ischemic stroke. The goal of this study is to evaluate the association between LA dilatation and reduced left ventricular ejection fraction (EF) with cardioembolic stroke. Methods: Four hundred fifty-three patients with ischemic stroke admitted to the University of California, Irvine between 2016-2017 were included based on the following criteria: age >18 and availability of echocardiogram. Stroke was categorized into cardioembolic and non-cardioembolic. EF was categorized into normal: 52-72% (male), 54-74% (female), mildly abnormal: 41-51% (male), 41-53% (female), moderately abnormal: 30-40%, and severely abnormal: <30%. LA volume was categorized into normal (≤34 ml/m2) versus enlarged (≥35 ml/m2). Other variables included gender, hypertension (SBP ≥140 or DBP ≥ 90), and known history of atrial fibrillation (Afib). Results: Two hundred eighteen patients had cardiomebmolic and 235 had non-cardioembolic stroke. Among patients with cardiomebmolic stroke, 49 (22.4%) and 142 (65%) had reduced EF and enlarged LA, respectively, as compared to 19 (8.1%) and 65 (27.7%) in patients with non-cardioembolic stroke (p <0.0001). The odds of cardioembolic stroke were 2.0 (95% CI: 0.1-6.0) and 8.8 times (95% CI: 1.9-42.3) higher in patients with moderately and severely reduced EF, respectively, when compared to patients with normal EF. The odds of cardioembolic stroke was 2.4 times (95% CI: 1.5-3.9) in patients with enlarged LA when compared to patients with normal LA size. Compared to the patients with normal LA and EF, patients with combined enlarged LA and reduced EF had significantly higher rates of Afib (43.4% versus 9.0%, p <0.0001) and cardioembolic stroke (78.3% versus 43.4%, p <0.0001). Conclusions: LA dilatation along with reduced EF are more reliable predictors of Afib and cardioembolic stroke. Further studies are warranted to determine the benefit of anticoagulation for secondary stroke prevention in such patient population.